IMPLEMENTASI NILAI-NILAI PANCASILA SEBAGAI PENDUKUNG TUMBUH KEMBANG WAWASAN KEBANGSAAN PADA MATA PELAJARAN PPKn DI SMP NEGERI 7 PALEMBANG - Danniarti, Rahma (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2017)
This study aimed at describing the implementation of Pancasila as the values which supported the improvement and development of national insight on PPKn subject in SMP Negeri 7 of Palembang. This research was a descriptive research using qualitative approach. It was conducted in SMP Negeri 7 Palembang involving the teachers and the students as the object of the research. The data were collected through observation, interviews, and documentation. The validity of the data was measured through triangulation technique. The results showed that students in SMP Negeri 7 began to show the attitude of nationalism, such as: respect for the dignity of human beings as the creation of the Almighty God by reading the holy verses of the Qur'an and Dhuha prayer at zero hour (06:40) ; helped a needy friend, dared to respond to what the teacher had taught. From this study, it is clear that Pancasila is really the foundation and the principal of life of the Indonesian nation. Through Pancasila and PPKn subject, the education in Indonesia is hoped to be able to create the generation whose attitudes and actions really reflect the identity of the Indonesian nation which is based on the values of Pancasila. It is also taught abou how to defend the country. If one region in Indonesia is threatened then the threat applies to all Indonesian citizens.